Entrepreneurship and Sustainable Livelihoods: A Pathway to Equitable Development - Mathur, Shweta (Victoria Journal of Management, 2025)
In the face of rising poverty, climate vulnerability and widening inequalities, sustainable and inclusive livelihood strategies are urgent. This paper analyzes the ways in which entrepreneurship Can support sustainable livelihoods and advance the broader objectives of sustainable development. With 61% of the global workforce in informal employment, entrepreneurial interventions can enhance human, social, natural, physical and financial capital. Case studies from India, Nepal and Sweden demonstrate entrepreneurship’s potential to reduce poverty, build local capacities and align livelihood development with the Sustainable Development Goals (SDGs). Women-led agro tourism in Nepal and renewable energy enterprises in Sweden showcase entrepreneurship’s contribution to economic resilience, gender empowerment and environmental sustainability. The paper analyzes differences between rural and urban livelihood strategies, challenges posed by urbanization and the role of technological innovations. Special emphasis is placed on empowering women and marginalized groups through access to credit, training and markets. Entrepreneurship, embedded within inclusive policy frameworks and supported by innovation and education, can drive sustainable development. Practical suggestions are provided for fostering entrepreneurship to build adaptive, resilient and sustainable livelihood systems in rural and urban contexts. By promoting entrepreneurship, policymakers and practitioners can unlock the potential of vulnerable populations, reduce poverty and promote sustainable development. This paper provides insights into the transformative power of entrepreneurship in achieving sustainable livelihoods and advancing the SDGs.